ANALISIS KARAKTERISTIK PEMBELAJARAN PADA MATERI PENCEMARAN DAN KERUSAKAN LINGKUNGAN - Hilya, Sofia; Khoironi Fanana Akbar; Riris Idiawati; Achmad Sofil Aqli (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2024)
This research aims to determine the learning characteristics of environmental pollution and damage material in science subjects. This research uses literature analysis to determine the characteristics of environmental pollution and damage at home and abroad, in terms of media and assessments to assess students' understanding of environmental pollution and damage material in learning. The literature studied comes from national and international journals covering the years 2014 to 2023. This research produces the conclusion of a literature review for empowering innovation in teaching materials and the form of assessment used on materials must be based on the characteristics of material pollution and environmental damage.